The Impact of the COVID-19 Pandemic on Affect, Fear, and Personality of Primary School Children Measured During the Second Wave of Infections in 2020 - Matiz, Alessio; Fabbro, Franco; Paschetto, Andrea; Urgesi, Cosimo; Ciucci, Enrica; Baroncelli, Andrea; Crescentini, Cristiano (Frontiers in Psychiatry, 2022)
In relation to the COVID-19 pandemic outbreak, a large body of research has identified a negative impact on individuals' affectivity, frequently documented by increased prevalence of anxiety and depression symptoms. For children, this research was less extensive, was mainly based on caregivers' reports and neglected personality assessment. In order to measure the impact of the pandemic, and the fears it caused, on primary school children's affect and personality, 323 (180 boys and 143 girls) Italian third, fourth and fifth graders were assessed between October and November 2020, namely during the second wave of COVID-19 infections in Italy, with validated self-reports of affect (Positive and Negative Affect Scale for Children, PANAS-C), fear of COVID-19 (Fear of COVID-19 Scale, FCV-19S) and personality (junior Temperament and Character Inventory, jTCI). In comparison with PANAS-C and jTCI normative scores collected prior to the pandemic, data obtained from children in 2020 showed unchanged affect scores in the overall sample, a decrease of Positive Affect in girls, and a decrease in the Harm Avoidance and an increase in the Self-Transcendence scales of personality. Fear of COVID-19 scores were positively correlated with Negative Affect scores and negatively predicted by children's personality profile of resilience (calculated using scores on the Harm Avoidance and the Self-Directedness scales of personality). These results suggested that Italian primary school children, especially boys, maintained their pre-pandemic levels of affect (or restored them after the first COVID-19 wave) and partially diverged from the typical development of personality in an apparently positive sense, namely toward more courageous/optimistic and spiritual profiles. This sort of children's post-traumatic growth might also be attributed to children's family and education systems, which should continue to be supported to promote and maintain community mental health.